2017
DOI: 10.1097/nan.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Best Nursing Practice for Implanted Ports

Abstract: Nearly 3 million central vascular access devices (CVADs) are used in the United States each year. These devices are an important advance in health care and essential to oncology patients. However, CVADs are the most frequent cause of central line-associated bloodstream infections (CLABSIs). CLABSI can be prevented when evidence-based practices are followed consistently over time. Professional organizations establish valid standards and guidelines to guide CVAD practice. This article identifies strategies imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, complications such as puncture failure, infection, catheter fracture, and extravasation can occur, potentially resulting in patient death. Good puncture technique and care are critical for catheter maintenance [ 5 , 6 , 7 , 8 ]. Injection through a Port-A catheter is an invasive procedure, and a good puncture greatly eliminates the damage to the catheter path [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, complications such as puncture failure, infection, catheter fracture, and extravasation can occur, potentially resulting in patient death. Good puncture technique and care are critical for catheter maintenance [ 5 , 6 , 7 , 8 ]. Injection through a Port-A catheter is an invasive procedure, and a good puncture greatly eliminates the damage to the catheter path [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Manias et al, 2003). A strategy for education and assessing clinical competence is essential to ensure compliance with the requirements for ongoing nursing registration guidelines that reduce unnecessary variation in practice and support better patient outcomes (Conley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recommended irrigation volume for an intravenous port according to the instruction manual and guidelines is 10 ml regardless of the intraluminal volume variations. [ 1 – 4 ] Therefore, we tried to quantify a recommended irrigation volume by the irrigation volume test. In our study, the ideal irrigation volume was found to be 20 times the intra-luminal volume of the implanted port, including the injection chamber and catheter lumen.…”
Section: Discussionmentioning
confidence: 99%
“…However, published guidelines and manufactures’ maintenance manuals recommend 10 ml normal saline irrigation volume for an intravenous port, regardless of the injection chamber size and implanted catheter length. [ 1 – 4 ]…”
Section: Introductionmentioning
confidence: 99%